2010
DOI: 10.1118/1.3468773
|View full text |Cite
|
Sign up to set email alerts
|

SU‐GG‐T‐376: Medical Physics Calculations in the Cloud: A New Paradigm for Clinical Computing

Abstract: Purpose: The accuracy of medical physics calculations is largely limited by the availability of fast computer hardware, which is in turn strongly limited by budget considerations. This research explores the use of the Cloud Computing paradigm to replace or supplement existing computing infrastructure for medical physics calculations. Cloud computing services allow for on‐demand virtual computing clusters with a pay‐as‐you‐go pricing model. This model has the potential to make large scale Monte Carlo simulation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Cloud computing (Armbrust et al , 2010) has the advantage that computational resources are provided “on-demand”. Keyes et al (2010) first ported dose calculations into a cloud environment and the computation time was explained by a theoretical model, demonstrating the efficiency improvement using multiple nodes. Poole et al (2012) found that the computation time decreases approximately with 1/ n , where n was the number of parallel machines used.…”
Section: Gpu Vs Other Architecturesmentioning
confidence: 99%
See 1 more Smart Citation
“…Cloud computing (Armbrust et al , 2010) has the advantage that computational resources are provided “on-demand”. Keyes et al (2010) first ported dose calculations into a cloud environment and the computation time was explained by a theoretical model, demonstrating the efficiency improvement using multiple nodes. Poole et al (2012) found that the computation time decreases approximately with 1/ n , where n was the number of parallel machines used.…”
Section: Gpu Vs Other Architecturesmentioning
confidence: 99%
“…However, the data communication overhead still remains. The available work (Keyes et al , 2010; Pratx and Xing, 2011b; Poole et al , 2012) showed that cloud computing is feasible for a MC dose calculation. This was possible, because the MC dose calculation is an embarrassingly parallel computing problem, in which inter-CPU data communication is very minimal.…”
Section: Gpu Vs Other Architecturesmentioning
confidence: 99%